Converging on strike revisited: Deregulation and the rise of low cost employment regimes in the European airline industry - Dieter Plehwe (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
Airline industry restructuring proceeded in high gear following the 9/11 attacks, which triggered a global air transport crisis in the beginning of the new millennium. European (network) legacy carriers have been reorganizing to meet low-cost challengers in European and new competition in global markets. The focus on employment relations and cost-oriented human resource management (HRM) has already been discussed back in the 1990s, pitching industry-level convergence arguments against diversity accounts on the one hand, and featuring different understandings and methodologies of comparative industrial relations (IR) on the other hand. A final comment to a controversy in the European Journal of Industrial Relations of 15 years ago pointed to the neglected dimension of increasing tensions and labor conflicts in the earlier debate, and thereby addressed an important commonality in the European industry's development during the late 1980s and early 1990s. This article revisits the debate to eventually treat the argument of convergence on strike as a set of hypotheses to be tested for the time after 1995. Apart from overall confirming the pattern of a high propensity to labor conflict in the airline industry I concur with Gall (1996) that the causes for relatively high levels of conflict can change over time. A better understanding of the reasons for the latest convergence on strike (2000s) is therefore considered the next frontier with evidence suggesting an overall growing segment of low-cost employment relations to explain the most recent waves of labor conflict and the cross national variation of employment relations in the industry. – – Die Angriffe vom 11. September 2001 in New York führten zu einer globalen Krise im Luftverkehr, in deren Folge sich erneut eine starke Restrukturierung der Luftverkehrsbranche vollzogen hat. Die traditionellen europäischen Netzwerklinien reorganisieren ihre Organisationsstrukturen, um auf die doppelte Herausforderung von Niedrigkosten-Fluglinien und neuen globalen Wettbewerbern zu reagieren. Der erneute Fokus auf Beschäftigungssysteme und kostenorientierten Personaleinsatz (Human Resource Management, HRM) wurde bereits in den 1990er Jahren diskutiert, wobei unterschiedliche Autoren Argumente für sektorale Konvergenz und anhaltende Divergenz in der Luftfahrtbranche ins Feld führten. Gleichzeitig offenbarte diese Debatte unterschiedliche theoretische und methodische Schwerpunkte der vergleichenden Forschung zu industriellen Beziehungen. Ein abschließender Kommentar zu einer Kontroverse, die in der Zeitschrift European Journal of Industrial Relations vor knapp 20 Jahren ausgetragen wurde, wies auf die in der Debatte bis dahin vernachlässigte Dimension zunehmender Spannungen und Konflikte im Arbeitsverhältnis hin. Damit wurde ein spezifischer gemeinsamer Aspekt in der Entwicklung der europäischen Luftverkehrsbranche während der späten 1980er und frühen 1990er Jahre angesprochen. Der vorliegende Beitrag rekapituliert die Debatte, um das Argument einer Konvergenz im Hinblick auf Arbeitskonflikte mit verschiedenen Hypothesen für die Zeit seit 1995 zu testen. Abgesehen von einer allgemeinen Bestätigung der anhaltenden Konflikthaftigkeit wird Gall (1996) dahingehend zugestimmt, dass sich die Ursachen für hohe Streikanfälligkeit im Laufe der Zeit wandeln können. Die neue Forschungsanforderung liegt in der Erklärung der erneut hohen Konfliktintensität im vergangenen Jahrzehnt, wobei diese wesentlich auf die Expansion von Beschäftigungsmodellen zu niedrigen Kosten zurückgeführt wird.
Keywords: 330; Airline industry; deregulation; human resource management; employment relations; industrial relations; low-cost model; collective action; convergence